Hygienic Aspects Of Sustainable Development Of Greenhouse Crop Production In Uzbekistan - Shakhoza, Iskandarova; Firdavs, Nurullaev; Natalia, Voronina; Umida, Nurullaeva; Mavlyuda, Shamsutdinova (Journal of Neonatal Surgery, 2025)
Greenhouse crop production in Uzbekistan plays a crucial role in ensuring food security and agricultural sustainability. However, its rapid expansion raises significant hygienic concerns, including soil and water contamination, pesticide exposure, and the impact of climate conditions on workers’ health. This article explores the hygienic aspects of sustainable greenhouse farming, emphasizing the importance of safe agricultural practices, effective waste management, and regulatory measures. The study highlights the necessity of integrating environmental hygiene principles into greenhouse production to promote health safety, reduce ecological risks, and enhance long-term sustainability. Recommendations for improving hygiene standards, optimizing resource use, and implementing innovative technologies are provided to support sustainable development in Uzbekistan’s greenhouse agriculture sector